Pengaruh Konten Kesehatan Mental pada Media Sosial Terhadap Kejadian Self-Diagnose di Tengah Masyarakat - Heira Muthia Ismed, Gabila (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Social media has become a major tool in discussing mental health, offering benefits such as increased awareness and reduced stigma. However, the phenomenon of self-diagnosing due to unverified information poses a major challenge. Individuals often diagnose themselves based on content on platforms such as TikTok and Instagram, without professional consultation. This practice can have negative repercussions, including misdiagnosis, excessive anxiety, and delaying appropriate medical help. Research shows that the use of social validation features on social media contributes to psychological risk, while the spread of inaccurate information exacerbates public misconceptions about mental disorders. Interventions through mental health literacy, content regulation, and professional consultation are needed to reduce these adverse impacts. Collaborative strategies between health professionals, communities and digital platforms can support more responsible use of social media for mental health issues.